Iron Rod Penetrating Head Injury in a Child - Diyora, Batuk; Gawali, Sagar; Patel, Mehool; Dhall, Gagan (Indian Journal of Neurotrauma, 2021)
Civilian penetrating brain injury (PBI) is a rare form of traumatic brain injury (TBI) and is rarer in the pediatric population. Pediatric PBI due to various objects has been reported in the literature. Pediatric PBI with an iron rod has not been previously described. We reported a case of civilian penetrating injury in a 6-year-old girl child patient who fell over a projecting iron rod at a construction site from a height of 6 to 8 feet. She was lifted off from the iron rod and taken to the emergency medical services. CT scan of the brain revealed linear intracerebral hemorrhage along the iron rod’s track with a depressed fracture. She underwent emergency surgery because of a compound depressed fracture. She recovered well from his injury without neurological deficit with an excellent clinical outcome.
Keywords: penetrating injury; children; head injury; iron rod; trauma